Game Multimedia tentang Sistem Tata Surya Berbasis Android sebagai Media Edukasi pada Anak Usia 6-12 Tahun - Alfarabi Helpendi; Eko Purnomo (Jurnal Riset Rumpun Seni, Desain dan Media, 2024)
The solar system is one of the materials from natural science lessons taught in elementary school. However, many students have difficulty understanding and memorizing material about the solar system because of the many different characteristics of each planet. This happens because of the limited learning media provided by the teacher when introducing parts of the solar system. The delivery of material to students must be with a fun method so that students are not easily bored and easy to understand every side of learning. games have great potential in educating children about the solar system, of course, using games that are fun and fun will be more effective for children to absorb all the information contained in the games they play. The design of this game uses the Design Thimgking method, so it can be concluded that this design is a problem originating from a sense of empathy, the need for a solution to an existing problem, then continue to test for improvement. Then the game is created as the main media, then accompanied by other supporting media such as Posters, X-Banners, Game Cards, Stickers, Keychain, and Pins.